Living Qur’an dan Etika Kepedulian Sosial: Implementasi Surah Al-Ma’un di Panti Asuhan An-Nur Medan Tembung - Said Fahrezi; Junaidi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
This article examines the implementation of the values of Surah Al-Ma’un at An-Nur Orphanage in Medan Tembung from the perspective of Living Qur’an studies. The study aims to analyze how the values of Surah Al-Ma’un are internalized, institutionalized, and manifested in social practices of caregiving and organizational relations within the orphanage. Employing a qualitative approach, the research utilizes observation, interviews, and documentation, analyzed through the framework of Living Qur’an and Qur’anic ethics. The findings reveal that Surah Al-Ma’un is not treated merely as a normative-ritual text but is lived as an ethical source shaping social concern, empathy, and solidarity within the institution. The internalization of these values occurs through religious habituation, the moral exemplarity of caregivers, and care-based institutional practices. However, the implementation remains largely confined to charity ethics and has not fully developed into a structurally oriented social justice ethic. This study contributes to Living Qur’an scholarship by highlighting the significance of institutional-level analysis and offering a reflective reading of Surah Al-Ma’un as a foundation for Qur’anic social ethics in the context of social transformation.